Comparative Study of Ondansetron and Granisetron for Preventing Post-Operative Nausea and Vomiting in Laparoscopic Cholecystectomy under General Anaesthesia - pradhan, Suresh; Dhakal, Santosh (Nepal Journal of Medical Sciences, 2021)
Introduction Post-operative nausea and vomiting are commonly experienced unpleasant complications of general anesthesia following laparoscopic surgeries. The study was undertaken to compare the antiemetic efficacy of two different 5-hydroxytryptamine-3 receptor antagonists, ondansetron and granisetron when given prophylactically to patients undergoing laparoscopic cholecystectomy under general anesthesia. Methods A prospective, double-blind study, was conducted in 60 patients aged 20-60 years ASA-PS I/II, weighing 40-80 kgs, undergoing elective laparoscopic cholecystectomy under general anesthesia. Patients were divided into two groups: Group A (Ondansetron 4mg intravenously) and Group B (Granisetron 2mg intravenously) with 30 patients in each group. Both the drugs were diluted in normal saline to 10 ml and were given at the end of surgery before the reversal of the neuromuscular blockade. Episodes of nausea and vomiting were assessed at 6, 12, and 24 hours post-operatively. Collected data was applied with the appropriate test in Statistical Package for the Social Sciences (SPSS) and p-value <0.05 was considered significant. Results Incidence of PONV was greater in Ondansetron group (53.33%) compared to Granisetron group (23.33%) (p=0.02). Demographic data were comparable in both groups (p>0.05). The episodes of retching and vomiting at different intervals were found to be higher in the ondansetron group. However, it was statistically insignificant. The use of rescue anti-emetics was greater in group A (13.33%) compared to group B (3.33%) but the finding was insignificant statistically (p=0.16). Conclusion The incidence of PONV was significantly high in the Ondansetron group than in the Granisetron group when given prophylactically in laparoscopic cholecystectomy.